Pemberdayaan Kelompok Wanita Tani Melalui Pelatihan Shibori untuk Meningkatkan Ekonomi Kreatif Desa Jaya Asri, Kecamatan Metro Kibang, Kabupaten Lampung Timur - M Ardi Rasyid; Prayoga Rakhmat Pratama; Rafa Febryan Nugraha Damhudi; Rafi Fauzul Haq; Pungki Amelia; Puspita Damayanti; Putri Rahma Sari; Putri Secilia; Putri Umi Kulsum; Rahma Wahida (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Empowering rural women through creative economic development is an important strategy in improving community independence and welfare. This study focuses on efforts to improve the skills of the Women Farmers Group (KWT) in Jaya Asri Village, Metro Kibang District, East Lampung, by providing training in tablecloth making based on the shibori technique. The method used is Participatory Action Research (PAR), which emphasizes the active involvement of KWT members in every stage of the activity. There were 12–15 participants, who were involved from the process of identifying needs, drafting plans, implementing training, observation, to evaluation. Data collection was carried out through participatory observation, in-depth interviews, and documentation. The collected data were analyzed qualitatively through reduction, presentation of information, and drawing conclusions, and reinforced through source triangulation techniques. The results of the study show that the training was able to improve basic shibori skills, build confidence, foster entrepreneurial motivation, and strengthen solidarity among group members. However, several obstacles were found that need to be addressed, such as limited technical mastery, limited training time, and suboptimal access to product marketing. These obstacles indicate the need for ongoing mentoring programs and institutional support so that the results of the training can continue to develop. The research conclusion confirms that shibori has the potential to be a gateway to creative economic development in villages. This potential can only be realized if it is supported by ongoing training, marketing support, and consistent institutional facilitation.